2006
DOI: 10.1002/hed.20524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artemisinin and its derivatives on growth inhibition and apoptosis of oral cancer cells

Abstract: The deoxoartemisinin trimer was found to have greater antitumor effect on tumor cells than other commonly used chemotherapeutic drugs, such as 5-FU, cisplatin, and paclitaxel. Furthermore, the ability of artemisinin and its derivatives to induce apoptosis highlights their potential as chemotherapeutic agents, for many anticancer drugs achieve their antitumor effects by inducing apoptosis in tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 19 publications
9
84
0
1
Order By: Relevance
“…DHA, a semi-synthetic derivative of the herbal antimalarial drug artemisinin, can obviously inhibit the growth of a variety of cancer cells, including breast cancer, leukemia, cervical cancer, ovarian cancer, lung cancer, gliomaand oral cancer (Jiao et al, 2007;Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Handrick et al, 2010). Our studies indicated that DHA inhibited the growth of A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…DHA, a semi-synthetic derivative of the herbal antimalarial drug artemisinin, can obviously inhibit the growth of a variety of cancer cells, including breast cancer, leukemia, cervical cancer, ovarian cancer, lung cancer, gliomaand oral cancer (Jiao et al, 2007;Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Handrick et al, 2010). Our studies indicated that DHA inhibited the growth of A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…DHA is shown to have anticancer effects in a wide variety of cancer models in vitro and in vivo (Jiao et al, 2007;Sun et al, 2014). Many studies have shown that DHA inhibits cell proliferation, and induces apoptosis in various human cancer cell lines via down-regulating cyclin (D1, E), Bcl-2, Bcl-xL, caspase-3, caspase-9 and VEGF, while up-regulating P21, P27 and Bax (Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Chen et al, 2010;Handrick et al, 2010). Therefore, the targeted efficacy of DHA on the TCTP expression of lung cancer cell was explored in the study.…”
Section: Targeted Efficacy Of Dihydroartemisinin For Translationally mentioning
confidence: 99%
“…The presence of activated caspase-3 indicates that apoptosis is at the irreversible stage [20] . Nam et al [21] found that artemisinin can induce apoptosis by up-regulating caspase-3. Our study also showed that the activity of caspase-3 in pancreatic acinar cells was obviously elevated after artemisinin was added, indicating that artemisinin may promote apoptosis.…”
Section: Research Frontiersmentioning
confidence: 99%
“…Yook (Yonsei University College of Dentistry, Korea) 14) , and cultured in an incubator at 5% CO2 and 37 o C, on T75 flasks using RPMI 1640 medium containing 5% fetal bovine serum (Hyclone, Logan, UT, USA) and 1% penicillin-streptomycin (Lonza, Allendale, NJ, USA).…”
Section: Cell Culturementioning
confidence: 99%